2019
DOI: 10.1016/j.rbo.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

O impacto da histologia do carcinoma pulmonar na frequência das metástases ósseas

Abstract: Objective  Lung cancer is the leading cause of death by cancer, and the bones are one of the most common sites of metastasis from this condition. This study aimed to evaluate the influence of lung carcinoma histology on the frequency of bone metastases. Methods  This retrospective study evaluated the medical records of 407 patients diagnosed with lung cancer between 2003 and 2012. The prevalence of bone metastases and their association with histological subtypes were evaluated using chi-squared tests, odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These aspects support previously published data regarding the histopathological types of lung cancer in Romania. Compared to other studies, from Asia or Latin America, which reported that lung adenocarcinoma was the primary origin of SM in 58.3%-69.6% of cases, and squamous cell carcinoma was associated with a much lower risk of bone metastasis, being identified only in 13%-17% of cases [32,33], statistical analyzes in Romania show that 48% of lung cancer patients have squamous cell lung carcinoma, 29% have adenocarcinoma, 7% have large cell carcinoma and 16% have small cell lung cancers [34]. These statistical data are also confirmed by the present study, in which the histological subtype of lung cancer that metastasizes at spinal level most frequently was squamous cell carcinoma.…”
Section: Discussioncontrasting
confidence: 67%
“…These aspects support previously published data regarding the histopathological types of lung cancer in Romania. Compared to other studies, from Asia or Latin America, which reported that lung adenocarcinoma was the primary origin of SM in 58.3%-69.6% of cases, and squamous cell carcinoma was associated with a much lower risk of bone metastasis, being identified only in 13%-17% of cases [32,33], statistical analyzes in Romania show that 48% of lung cancer patients have squamous cell lung carcinoma, 29% have adenocarcinoma, 7% have large cell carcinoma and 16% have small cell lung cancers [34]. These statistical data are also confirmed by the present study, in which the histological subtype of lung cancer that metastasizes at spinal level most frequently was squamous cell carcinoma.…”
Section: Discussioncontrasting
confidence: 67%
“…Outra diferença mostrada é que em homens residentes nas capitais dos estados brasileiros, quando comparado com o interior, possuem taxas de mortalidade inferior, muito em função da também queda da prevalência de fumantes, uma vez que esse tipo de câncer possui letalidade alta (SILVA et al, 2020). Em virtude de ser uma doença agressiva, o câncer de pulmão já possui um prognóstico ruim, mas quando acometido por metástases esse prognóstico fica ainda pior, além de afetar a qualidade de vida dos pacientes (OLIVEIRA et al, 2019). As metástases ósseas (MOs) são as mais frequentes em casos de câncer de pulmão, chegando em aproximadamente 30% em pacientes com CA de pulmão de não pequenas células e são associadas a idade, sexo, etnia, tabagismo e histologia do câncer (BESSA et al, 2022).…”
Section: Resultsunclassified
“…11,12 The three most commonly described locations of lung cancer metastases are the spine, pelvis, and femur. 13 Metastasis of primary lung cancer to the bone below the knee and elbow is very rare and requires a multidisciplinary team approach to establish the correct diagnosis and treatment. 14 Although bone metastases are common in patients with cancer, isolated ulnar metastases are extremely rare or have never been reported.…”
Section: Discussionmentioning
confidence: 99%